Polyphenol-Modified Starches and Their Applications in the Food Industry: Recent Updates and Future Directions - Ngô Văn Tài; Sandra Kusumawardani; Kannika Kunyanee; Naphatrapi Luangsakul (Foods, 2022)
Health problems associated with excess calories, such as diabetes and obesity, have become serious public issues worldwide. Innovative methods are needed to reduce food caloric impact without negatively affecting sensory properties. The interaction between starch and phenolic compounds has presented a positive impact on health and has been applied to various aspects of food. In particular, an interaction between polyphenols and starch is widely found in food systems and may endow foods with several unique properties and functional effects. This review summarizes knowledge of the interaction between polyphenols and starch accumulated over the past decade. It discusses changes in the physicochemical properties, in vitro digestibility, prebiotic properties, and antioxidant activity of the starch-polyphenol complex. It also reviews innovative methods of obtaining the complexes and their applications in the food industry. For a brief description, phenolic compounds interact with starch through covalent or non-covalent bonds. The smoothness of starch granules disappears after complexation, while the crystalline structure either remains unchanged or forms a new structure and/or V-type complex. Polyphenols influence starch swelling power, solubility, pasting, and thermal properties; however, research remains limited regarding their effects on oil absorption and freeze-thaw stability. The interaction between starch and polyphenolic compounds could promote health and nutritional value by reducing starch digestion rate and enhancing bioavailability; as such, this review might provide a theoretical basis for the development of novel functional foods for the prevention and control of hyperglycemia. Further establishing a comprehensive understanding of starch-polyphenol complexes could improve their application in the food industry.
Keywords: Food composition and properties; Microbial Metabolites in Food Biotechnology; Polysaccharides Composition and Applications